Search for evidence of introgression of wheat (Triticum aestivum L.) traits into sea barley (Hordeum marinum s.str. Huds.) and bearded wheatgrass (Elymus caninus L.) in central and northern Europe, using isozymes, RAPD and microsatellite markers - Guadagnuolo, Roberto; Savova Bianchi, Dessislava; Keller-Senften, J.; Felber, François (My University, 2001)
Seeds of English and Austrian populations of bearded wheatgrass (Elymus caninus L.) and sea barley (Hordeum marinum Huds.) growing in the vicinity of wheat (Triticum aestivum L.) fields were collected in order to search for evidence of the introgression of wheat traits into these wild relatives. Seeds were sown and plants grown for subsequent analyses using morphological and genetic (isozymes, RAPD and wheat microsatellites) markers. No F1 hybrids were found within the individuals of the two species grown, neither with morphological nor with genetic markers. Also, no evidence of introgression of wheat traits into E. caninus was observed. However, in one individual of H. marinum which had the typical morphology of this species, numerous species-specific DNA markers of wheat were amplified, thereby demonstrating previous hybridization. Consequently, the hybridization between wheat and H. marinum under natural conditions and the introgression of wheat traits into this wild relative seems to be possible. Our results contribute to the risk assessment of transgenic wheat cultivation.
Keywords: wheat; wild relative; gene flow; introgression; genetic marker